Analysis of students with the wrong major based on the metacognitive dimension - Suharno Suharno; Fudiana Lailaturrohmah; Purwanto Purwanto; Ranto Ranto; Muhammad Akhyar (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
Precisely, students with the wrong major faced several conflicts such as academics. To improve education quality, it is necessary to develop metacognitive skills because the level is still in the risk category. Therefore, this study aims to analyze (1) the percentage of students with the wrong major (2) the impact and factors that cause children to select the wrong majors (3) students' learning activities with the wrong major. The design is descriptive and quantitative with questionnaires distributed in three batches. Furthermore, the test was carried out using proportional stratified random sampling. Data were collected through questionnaires and interviews. The validity test was performed using the product moment method from Karl Person. Moreover, data were analyzed by employing factors and descriptive statistical techniques. The results showed that; First, 59% and 41% of students agree and refused they are in the wrong major. Second, the influencing factors include seeking opportunities to enter college, degree demand in the work context, parental coercion, study program profiles, and job prospects. However, the most influencing factor is seeking opportunities to enter college. Third, the wrong study program causes students to feel inferior to others. Fourth, there is a negative influence of the wrong major on metacognitive, particularly in planning development where children have difficulty managing time to achieve their goals.